Do weekend plan standard forms improve communication and influence quality of patient care?. Issue 958 (5th August 2005) - Grainge, C; Traer, E; Fulton, J
Abstract : Weekends are critical times in an inpatient stay, when daily review of patients is not routine and the usual team of doctors responsible for a patient's care is often not available. Communication between the patient's own doctors and the on call team is vital for continuity of care and to maintain patient safety. The provision and completeness of weekend plans was assessed before and after the introduction of a standard form. The introduction of the form led to a significant improvement in the proportion of notes containing a weekend plan and the proportion of notes containing a resuscitation decision (p<0.05), which will have a significant impact on patient care.